2016
DOI: 10.1093/chemse/bjw117
|View full text |Cite
|
Sign up to set email alerts
|

The Broadly Tuned Odorant Receptor OR1A1 is Highly Selective for 3-Methyl-2,4-nonanedione, a Key Food Odorant in Aged Wines, Tea, and Other Foods

Abstract: Key food odorants are the most relevant determinants by which we detect, recognize, and hedonically evaluate the aroma of foods and beverages. Odorants are detected by our chemical sense of olfaction, comprising a set of approximately 400 different odorant receptor types. However, the specific receptor activity patterns representing the aroma percepts of foods or beverages, as well as the key food odorant agonist profiles of single-odorant receptors, are largely unknown. We aimed to establish comprehensive key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 54 publications
3
70
0
3
Order By: Relevance
“…59,78 Other ORs were found to be more broadly tuned in their response to thiols and KFOs. 23a,71,79a When a family of 3-mercapto-2-methylalkan-1-ols were tested against OR2M3 using a cAMP luminescence assay, it was found that three substances with chain lengths C4–C6 activated OR2M3 in a specific and concentration-dependent manner. Homologues with C-atom chain lengths less than four and greater than six did not activate OR2M3.…”
Section: Demonstration Of the Activation Of Olfactory Receptors By mentioning
confidence: 99%
See 1 more Smart Citation
“…59,78 Other ORs were found to be more broadly tuned in their response to thiols and KFOs. 23a,71,79a When a family of 3-mercapto-2-methylalkan-1-ols were tested against OR2M3 using a cAMP luminescence assay, it was found that three substances with chain lengths C4–C6 activated OR2M3 in a specific and concentration-dependent manner. Homologues with C-atom chain lengths less than four and greater than six did not activate OR2M3.…”
Section: Demonstration Of the Activation Of Olfactory Receptors By mentioning
confidence: 99%
“…21b Anosmics may still be able to “smell” ammonia, since their CN V may still be functioning, although in some cases with decreased sensitivity. 79b …”
Section: Demonstration Of the Activation Of Olfactory Receptors By mentioning
confidence: 99%
“…The perception of odors of all kinds is initiated by binding to G protein-coupled receptors (GPCRs), encoded by about 400 odorant receptor (OR) genes [1][2][3], of which at least 270 appear to be expressed in the cilia of olfactory sensory neurons (OSNs) within the main olfactory epithelium (OE) of the nasal cavity [4]. Odor coding is then achieved in a combinatorial manner whereby more ORs are broadly tuned than narrowly tuned and whereby one odorant may activate multiple ORs [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the thiol-responsive human ORs identified, so far are members of family 2 of ORs [5, 6, 11-13, 31, 49]. Recently, we identified one narrowly tuned thiol-responding human receptor, OR2M3, as well as two broadly tuned receptors with overlapping thiol agonist spectra [5,6]. One causative mechanism for differences in tuning breadth may be the size of the respective ligand-binding pockets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation